Ultrasound molecular imaging of arterial thrombi with novel microbubbles modified by cyclic RGD in vitro and in vivo - Hu, Guangquan; Liu, Cheng; Liao, Yulin; Yang, Li; Huang, Ruizhu; Wu, Juefei; Xie, Jiajia; Bundhoo, Kaviraj; Liu, Ying; Bin, Jianping (Thrombosis and Haemostasis, 2012)
Despite immense potential, ultrasound molecular imaging (UMI) of arterial thrombi remains very challenging because the high-shear arterial flow limits binding of site-targeted microbubbles to the thrombi. The linear Arg-Gly-Asp (RGD) peptides have been successfully applied to evaluate venous, atrial, and arteriolar thrombi, but have thus far failed in the detection of arterial thrombi. Cyclic RGD (Arg-Gly-Asp-D-Phe-Cys) is a cyclic conformation of linear RGD peptides, which has much higher binding-affinity and selectivity for binding to the glycoprotein (GP) IIb/IIIa receptor than its linear counterpart and thus is likely to be an optimal targeted molecular probe for ultrasound molecular imaging of arterial thrombi. In this study, we sought to assess the feasibility of a novel microbubble conjugated with cyclic RGD (Mb-cyclic RGD) in UMI of arterial thrombi in vitro and in vivo. As expected, Mb-cyclic RGD had greater GP IIb/IIIa-targeted binding capability in all shear stress conditions. In addition, the shear stress at half-maximal detachment of Mb-cyclic RGD was 5.7-fold higher than that of microbubbles with nonspecific peptide (Mb-CON) (p<0.05). Mb-cyclic RGD enhanced the echogenicity of the platelet-rich thrombus in vitro whereas Mb-CON did not produce enhancement. In the in vivo setting, optimal signal enhancement of the abdominal aortic thrombus was displayed with Mb-cyclic RGD in all cases. Mean video intensity of the abdominal aortic thrombi with Mb-cyclic RGD was 3.2-fold higher than that with Mb-CON (p<0.05). The novel Mb-cyclic RGD facilitated excellent visualisation of arterial thrombi using UMI and showed great promise for clinical applications.
Keywords: Ultrasound molecular imaging; arterial thrombus; cyclic RGD; microbubbles